Effects of cinnamon extract on blood sugar levels of type 2 diabetes mellitus patients: Randomized Controlled Trial (RCT) - Dilma'aarij Agustia; Sutan Sahala Muda Marpaung; Dita Anggriani Lubis (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Cinnamon is an herbal remedy proven to lower blood sugar levels in patients with type 2 diabetes mellitus (DM). Cinnamon contains coumarin, which reduces the blood sugar levels. This study aimed to determine whether administration of a higher dose of cinnamon could lower blood sugar levels in individuals with type 2 diabetes mellitus. Methods: This study employed a randomized controlled trial (RCT) design and was conducted at the Medan Denai Health Center from November to December 2023. Participants were randomly selected and divided into two groups: the intervention group, which received cinnamon extract (n= 15), and the control group (n= 15), which did not receive any treatment. The dose was 10 mg/day. Blood sugar levels were measured using a standardized instrument and data were analyzed using the Kruskal–Wallis test. Results, before receiving cinnamon extract, the average blood sugar level was 238,80 mg/dL in the intervention group and 225,33 mg/dL in the control group. After cinnamon extract administration, the intervention group showed a significant reduction of 127,73 mg/dL, whereas that of the control group remained at 222,20 mg/dL. Statistical analysis revealed a significant difference in the blood sugar levels following cinnamon extract administration (p< 0,001). In conclusion, cinnamon extract supplementation can help lower blood sugar levels in patients with type 2 diabetes mellitus.